HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN DI DESA NEGERI AGUNG KECAMATAN RAMBANG KABUPATEN MUARA ENIM - Aulia, Sindy; Nurlaila; Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Parental parenting plays an important role in supporting the cognitive development of early childhood, especially for children aged 4–5 years who are in a critical period of development. This study aims to examine the relationship between parental parenting and the cognitive development of children aged 4–5 years in Negeri Agung Village, Rambang District, Muara Enim Regency. The research uses a quantitative approach with a correlational design. The sample consisted of 42 parents, selected using a total sampling technique. Data were collected through parental parenting questionnaires and observations of children’s cognitive development, then analyzed using the Pearson Product Moment correlation test and t-test at a 0.05 significance level. The analysis results show a correlation coefficient of 0.665 with a significance value of 0.000 < 0.05, indicating a positive and significant relationship between parental parenting and the cognitive development of children aged 4–5 years.